Virus Need of Achievement Pada Motivasi Beragama BJ Habibie dalam Novel Ainun-Habibie - Rusdi Kasman; Siti Maria Huaida (Prophetic guidance and counseling journal, 2022)
The purpose of this research is to find out the Need Achevement Virus on BJ Habibie's religious motivation in the novel Ainun Habibie. The aspects of religious motivation focused on in this research are aspects of religious nature and obligations; aspects of obtaining peace and safety; aspects of overcoming frustration; aspects of fulfilling social demands; and aspects of getting praise, prestige and prestige. This type of research is library research, with a qualitative research approach. The primary data source is the novel Ainun Habibie. Data analysis uses content analysis with stages including data collecting, data display, data reducing and conclusion and verification. The results showed that BJ Habibie's religious motivation in the aspect of nature and obligation showed a good religious motive; in the motive of obtaining peace, safety to overcome frustration showed a good religious motive; in the aspect of religious motives to fulfil social demands showed a fairly good religious motive; and in religious motives to get praise, prestige and prestige showed a fairly good religious motive. Abstrak Tujuan penelitian ini adalah untuk mengetahui Virus Need Achevement pada motivasi beragama BJ Habibie dalam novel Ainun Habibie. Aspek motivasi beragama yang difokuskan dalam penelitian ini adalah aspek fitrah dan kewajiban beragama; aspek memperoleh ketenangan dan keselamatan; aspek mengatasi frustasi; aspek memenuhi tuntutan sosial; dan aspek mendapatkan pujian, gengsi dan prestise. Jenis penelitian ini adalah penelitian pustaka, dengan pendekatan penelitian kualitatif. Sumber data primer adalah novel Ainun Habibie. Analisis data menggunakan content analysis dengan tahapan meliputi data collecting, data display, data reducing dan conclusion and verification. Hasil penelitian menunjukkan bahwa dorongan motivasi beragama BJ Habibie pada aspek fitrah dan kewajiban menunjukkan motif beragama yang baik; pada motif memperoleh ketenangan, keselamatan mengatasi frustasi menunjukkn motif beragama yang baik; pada aspek motif beragama untuk memenuhi tuntutan sosial menujukkan motif beragama yang cukup baik; dan pada motif beragama untuk mendapatkan pujian, gengsi dan prestise menujukkan motif beragama yang cukup baik.